2017
DOI: 10.1371/journal.pone.0170997
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Cytogenetics between Two Important Songbird, Models: The Zebra Finch and the Canary

Abstract: Songbird species (order Passeriformes, suborder Oscines) are important models in various experimental fields spanning behavioural genomics to neurobiology. Although the genomes of some songbird species were sequenced recently, the chromosomal organization of these species is mostly unknown. Here we focused on the two most studied songbird species in neuroscience, the zebra finch (Taeniopygia guttata) and the canary (Serinus canaria). In order to clarify these issues and also to integrate chromosome data with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 48 publications
4
50
0
Order By: Relevance
“…Besides the confirmation of breakpoints of ancient syntenic groups, one of the most interesting findings is the detection of both paracentric and pericentric inversions in the ancestral pair 1 (GGA1q), observed both in Oscines and Suboscines [Kretschmer et al, 2014dos Santos et al, 2015dos Santos et al, , 2017. As the results in Suboscines were based on only 1 species, E. spectabilis , our data confirm that these inversions are present in different subfamilies among Tyrannidae and must have occurred before the separation of Suboscines and Oscines, 20 million years ago [Ohlson et al, 2013].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Besides the confirmation of breakpoints of ancient syntenic groups, one of the most interesting findings is the detection of both paracentric and pericentric inversions in the ancestral pair 1 (GGA1q), observed both in Oscines and Suboscines [Kretschmer et al, 2014dos Santos et al, 2015dos Santos et al, , 2017. As the results in Suboscines were based on only 1 species, E. spectabilis , our data confirm that these inversions are present in different subfamilies among Tyrannidae and must have occurred before the separation of Suboscines and Oscines, 20 million years ago [Ohlson et al, 2013].…”
Section: Discussionsupporting
confidence: 75%
“…sulphuratus and S. subcristata have macrochromosomes with the same morphology, despite different diploid numbers. The analyses of classical cytogenetic data and FISH experiments show that these species retain a chromosome formula which is similar not only to other Tyrannidae, but also to other Oscines, with the first pair being submetacentric (corresponding to GGA2) and the presence of a centric fission in the ancestral pair 1, followed by a number of paracentric inversions, especially in the segment corresponding to GGA1q [Gunski et al, 2000;Kretschmer et al, 2014Kretschmer et al, , 2015dos Santos et al, 2015dos Santos et al, , 2017. Thus, the difference of diploid numbers must be due to rearrangements involving microchromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The domestic fowl, Gallus gallus (GGA), 2n = 78, was the first bird species from which WCPs were isolated [Griffin et al, 1999]. These GGA probes have been used successfully to determine the chromosomal homologies between distantly related species such as ostrich ( Struthio camelus ), American rhea ( Rhea americana ), canary ( Serinus canaria ), and zebra finch ( Taeniopygia guttata ) [Nishida-Umehara et al, 2007;dos Santos et al, 2017]. For example, chromosome painting with GGA probes in eagles (Accipitridae) has shown that the macrochromosomes of these birds evolved through interchromosomal rearrangements such as fusions, fissions, and chromosome transloca-tions, leading to a decrease in the diploid number to 58-68 [de Oliveira et al, 2005].…”
mentioning
confidence: 99%